Local governments in the wake of demographic change: evidence from German municipalities; Dezentrale Regierungen im Strudel von demographischen Wandel: Evidenz von deutschen Stadtverwaltungen - Benny Geys; Friedrich Heinemann; Alexander Kalb (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
German municipalities are expected to suffer from intense demographic changes in the upcoming decades; not only in the form of population losses, but also through a changing demographic structure (i.e. less children and adolescents, more elderly, higher dependency ratio, and so on). We assess local governments' vulnerability to the fiscal consequences of these demographic transformations (using a sample of 1021 municipalities in the state of Baden-Württemberg) by determining the elasticity of local government cost functions to municipalities' demographic characteristics. Our findings indicate that smaller municipalities are especially vulnerable to increasing cost pressures following most of the currently predicted demographic changes. In the absence of increased higher-level government support (e.g. through the fiscal equalization scheme), these findings would support a case for boundary reviews or more extensive inter-communal cooperation. – – Deutsche Stadtverwaltungen werden erwartungsgemäß in den kommenden Jahrzehnten unter einem demographischen Wandel zu leiden haben, welcher nicht nur in Form eines allgemeinen Bevölkerungsrückgangs, sondern auch durch einen Wandel in der demographischen Struktur (d.h. veränderte Altersstruktur durch weniger Junge und mehr Alte, höhere Abhängigkeitsrate usw.) zum Ausdruck kommt. Wir untersuchen die diesbezügliche Anfälligkeit von dezentralen Regierungen (zugrunde liegt eine Stichprobe von 1021 Stadt- und Gemeindeverwaltungen im Land Baden-Württemberg), indem wir die Elastizität der Kostenfunktionen bezüglich der demographischen Charakteristika der jeweiligen Stadt- und Gemeindeverwaltungen bestimmen. Unsere Ergebnisse deuten darauf hin, dass gerade kleinere Gemeinden unter dem steigenden Kostendruck leiden, der mit den meisten vorhergesagten demographischen Veränderungen einhergeht. Wenn keine übergeordnete Regierungsebene diese kleineren Verwaltungsgebiete unterstützt (z.B. durch ein Finanzausgleichsystem), dann unterstützen unsere Ergebnisse eine kritische Überprüfung von fiskalischen Grenzen bzw. der Ausweitung der inter-kommunalen Kooperation.
Keywords: H72; J11; 330; Demographic change; local government expenditures; cost elasticity; economies of scale; rolling regression; German municipalities